Environmental Justice in Intra Generations: An Overview of Aristotle's Distributive Justice to Coal Mining - Endyka, Yovi Cajapa; Muhdar, Muhamad; Sabaruddin, Abdul Kadir (Indonesian Comparative Law Review, 2020)
Indonesia is a country with abundant natural resources, ranging from sand. Tin, copper, coal, iron ore to gold. Therefore, the State should provide environmental justice to create reserves with wise and sustainable management of natural resources. This study uses a doctrinal method in order to answer the problem under study. This study will examine how Aristotle's distributive justice can sharpen the concept of justice for coal mining management. This study will focus on environmental justice in intra-generational terms in terms of Aristotle's distributive justice to coal mining. Protection of access (conservation of access) reflects the allocation of rights and access to natural resources balanced between different generations and fellow members of the current generation. Thus, access to protection provides fair and non-discriminatory rights for every citizen of the current generation to use environmental resources. However, in using these resources, each member of the current generation has an obligation (equitable duties) to ensure that his actions will not reduce future generations' access to these resources. The state through mining or environmental policies has not provided justice for the community, where the community accepts more risks such as social injustice, environmental and health harm from coal mining activities than receiving the benefits.